Pelatihan Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Berbasis Artificial Intelligence (AI) bagi Guru di SMA Negeri 1 Ciampel Karawang: Penelitian - Sumarta; H. Acep Bahrum Kamil; Fauzi Miftakh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The development of Artificial Intelligence (AI) technology provides significant opportunities in education; however, its utilization by teachers remains limited. This community service activity aimed to enhance the competencies of teachers at SMA Negeri 1 Ciampel Karawang in utilizing AI for developing effective, creative, and innovative lesson plans. The implementation methods included: (1) training on AI platform usage (ChatGPT, Canva AI, Grammarly); (2) mentoring in AI-based lesson plan development; and (3) evaluation of implementation results. The activity involved 20 teachers from various subjects. Results demonstrated: (1) a 78.5% increase in teachers' understanding of AI in education based on pre-test and post-test; (2) completion of 20 innovative AI-based lesson plans with average quality score of 85.1 (Excellent); (3) increased teacher satisfaction with lesson plan development ease scoring 4.60/5.0. This activity contributes to improving the quality of learning planning and promoting technology integration in teaching and learning activities in the digital era.